Translation initiation landscape profiling reveals hidden open-reading frames required for the pathogenesis of tomato yellow leaf curl Thailand virus. Issue 5 (26th January 2022) - Chiu, Ching-Wen; Li, Ya-Ru; Lin, Cheng-Yuan; Yeh, Hsin-Hung; Liu, Ming-Jung
Abstract: Plant viruses with densely packed genomes employ noncanonical translational strategies to increase the coding capacity for viral function. However, the diverse translational strategies used make it challenging to define the full set of viral genes. Here, using tomato yellow leaf curl Thailand virus (TYLCTHV, genus Begomovirus ) as a model system, we identified genes beyond the annotated gene sets by experimentally profiling in vivo translation initiation sites (TISs). We found that unanticipated AUG TISs were prevalent and determined that their usage involves alternative transcriptional and/or translational start sites and is associated with flanking mRNA sequences. Specifically, two downstream in-frame TISs were identified in the viral gene AV2 . These TISs were conserved in the begomovirus lineage and led to the translation of different protein isoforms localized to cytoplasmic puncta and at the cell periphery, respectively. In addition, we found translational evidence of an unexplored gene, BV2 . BV2 is conserved among TYLCTHV isolates and localizes to the endoplasmic reticulum and plasmodesmata. Mutations of AV2 isoforms and BV2 significantly attenuated disease symptoms in tomato ( Solanum lycopersicum ). In conclusion, our study pinpointing in vivo TISs untangles the coding complexity of a plant viral genome and, more importantly, illustrates the biological significance of the hidden open-reading frames encoding viral factors for pathogenicity. Abstract : Profiling translation initiation sites in plant begomoviruses reveals the complexity and diversity of plant virus coding capacity and uncovers the hidden open-reading frames required for pathogenesis.